Research of the possibility of monitoring the element composition in technological flows by prompt gamma-radiation at neutrons capture - Kurbanov, Bakhtiyar I.; Jurakulov, Alisher R.; Muzafarov, Amrullo M. (Journal of the Belarusian State University. Ecology, 2020)
This report presents the results of a study of the possibility of controlling the elemental composition in technological streams by instantaneous gamma radiation of neutron capture. An experimental setup based on a radionuclide (252Cf) neutron source has been assembled, the spectrometric system consists of a semiconductor Ge detector and a multi-channel pulse analyzer. A method has been developed for determining the concentration of components of complex mixtures.
Keywords: neutron capture; instant gamma radiation; elemental composition; radionuclide source; process stream; concentration; expressness of analysis